The Role of the University in Building the University Student’s Personality: A Field Study on Students at the University of Benghazi (Abhat Journal, 2024)
The study aimed to identify the role of the university in building the personality of the Libyan university student and the most aspects of the personality (cognitive - skillful - emotional) that the university builds in the student and to identify the influence of the variable (the “first and last” semesters) on the role of the university on the personality of the students as it aimed. To identify the nature of the student’s personality and to identify the effect of each of the variables (gender “male-female” - scientific specialization “humanities - applied sciences”) on the nature of the student’s personality. The study sample consisted of (506) male and female students in the colleges: (Engineering - Education - Economics - Science) affiliated with the University of Benghazi. Two tools were used to achieve the objectives of the study: a questionnaire on the role of the university in building the personality of the Libyan university student, prepared by the research group, and a scale of the five major factors of personality, prepared by Costa Macri. The study concluded that the following results:- The university has a prominent role in building the university student’s personality, especially on the cognitive, then skillful, then emotional aspects.- The study recommends activating the university's role in developing the student's personality in all its aspects.
Keywords: Character building; the role of the university; the university student